Effects of the New Aldose Reductase Inhibitor Benzofuroxane Derivative BF-5m on High Glucose Induced Prolongation of Cardiac QT Interval and Increase of Coronary Perfusion Pressure - C. Di Filippo; B. Ferraro; R. Maisto; M. C. Trotta; N. Di Carluccio; S. Sartini; C. La Motta; F. Ferraraccio; F. Rossi; M. D’Amico (Journal of Diabetes Research)
This study investigated the effects of the new aldose reductase inhibitor benzofuroxane derivative 5(6)-(benzo[d]thiazol-2-ylmethoxy)benzofuroxane (BF-5m) on the prolongation of cardiac QT interval and increase of coronary perfusion pressure (CPP) in isolated, high glucose (33.3 mM D-glucose) perfused rat hearts. BF-5m was dissolved in the Krebs solution at a final concentration of 0.01 μM, 0.05 μM, and 0.1 μM. 33.3 mM D-glucose caused a prolongation of the QT interval and increase of CPP up to values of 190 ± 12 ms and 110 ± 8 mmHg with respect to the values of hearts perfused with standard Krebs solution (11.1 mM D-glucose). The QT prolongation was reduced by 10%, 32%, and 41%, respectively, for the concentration of BF-5m 0.01 μM, 0.05 μM, and 0.1 μM. Similarly, the CPP was reduced by 20% for BF-5m 0.05 μM and by 32% for BF-5m 0.1 μM. BF-5m also increased the expression levels of sirtuin 1, MnSOD, eNOS, and FOXO-1, into the heart. The beneficial actions of BF-5m were partly abolished by the pretreatment of the rats with the inhibitor of the sirtuin 1 activity EX527 (10 mg/kg/day/7 days i.p.) prior to perfusion of the hearts with high glucose + BF-5m (0.1 μM). Therefore, BF-5m supplies cardioprotection from the high glucose induced QT prolongation and increase of CPP.